Ultrasound-guided microwave ablation for secondary hyperparathyroidism: a systematic review and meta-analysis - Xiaofeng Zhou; Yang Shen; Ying Zhu; Qiang Lv; Weiyu Pu; Leiping Gao; Mingjia Gu; Chao Li (International Journal of Hyperthermia, 2021)
Objectives Microwave ablation (MWA) is used for the treatment of severe secondary hyperparathyroidism (SHPT), but its efficacy and safety still remained unclear. This study aimed to investigate the efficacy and safety of ultrasound (US)-guided MWA in patients with SHPT. Methods The PubMed, Cochrane library, Embase, China national knowledge infrastructure (CNKI) and Wanfang databases were searched to identify published studies that evaluated the efficacy and safety of US-guided MWA in patients with SHPT. The primary outcomes were parathyroid hormone (PTH), serum calcium and phosphorus levels. Results A total of 26 studies with 932 patients were identified. The PTH levels showed significant reduction at 1 month [weighted mean difference (WMD) = 945.33, 95% CI: 797.15∼1093.52] and 6 months (WMD = 1,151.91, 95% CI: 990.93∼1312.89) after MWA of SHPT patients. The serum calcium (WMD = 0.39, 95% CI: 0.30 ∼ 0.48) and phosphorus levels (WMD = 0.64, 95% CI: 0.43 ∼ 0.85) showed significant reduction at 6 months after MWA of SHPT patients. The most common complications observed were hypocalcemia (35.2%) and transient hoarseness (9.2%). No other major complications or death occurred in our study patients. Conclusion These findings suggest MWA as a safe and effective minimally invasive technique for the management of SHPT. PTH, calcium, and phosphorus levels were significantly reduced at 1 and 6 months after MWA.